Correlation of Color Symbolism in Guel Dance Costumes and Movement in The Gayo Community - Permata, Magfhirah Murni Bintang; Setiawan, Indra (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
The Guel Dance, a traditional performing art originating from the Gayo culture in Central Aceh, Indonesia, is a captivating yet underappreciated cultural heritage. Although the dance is practiced within the community, many remain unfamiliar with its intricate visual and symbolic elements, such as the elaborate costumes, decorative patterns, properties (ulen-ulen), and especially the use of specific colors. These colors go beyond mere ornamentation—they act as visual metaphors and spiritual expressions, communicating profound cultural values. In Gayo culture, visuality is deeply meaningful and not simply decorative. Each design and color carries symbolic significance, inherited and sustained through generations, forming a rich semiotic system. The kerawang embroidery, a hallmark of Gayo visual identity, exemplifies this symbolic tradition. Despite its cultural importance, the role of color in the Guel Dance remains largely misunderstood by both dancers and musicians, often resulting in performances that lack harmony between costume visuals and dance expression. This research seeks to uncover and clarify the functions and meanings of visual elements—particularly color—in the performance of the Guel Dance. It investigates how colors and patterns in costumes are interwoven with movement, spiritual values, and ritual practices of the Gayo people. Employing a descriptive qualitative approach with a visual ethnographic model, the study documents how visual elements function in artistic performances and cultural rituals. This research identifies five primary colors in Guel dance costumes—red (courage), green (fertility), yellow (wisdom), black (authority), and white (purity). These colors are not arbitrary; they correspond to specific movements and spiritual expressions within the dance. The findings contribute to a deeper understanding of the cultural meanings embedded in Gayo traditional arts and emphasize the need for preserving and recontextualizing these values through synchronized and informed performances.